KAJIAN KERAGAAN KARAKTERISTIK DAN TINGKAT PENGETAHUAN PETANI TENTANG SISTEM INTEGRASI SAPI DAN KELAPA SAWIT (SISKA) DI KECAMATAN PANGKALAN LESUNG, KABUPATEN PELALAWAN - Susy Edwina; Evy Maharani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
Cattle development through regional integration system of oil palm plantations has a great opportunity to be developed. The idea of integration of beef  cattle  breeding  business  can  overcome  the  problem  of  land  scarcity. application of SISKA by Group Maju Bersama in the village of Bukit Harapan Siak  has  reached  the  stage  of  independence,  but  the  number  of  farmers  who have applied SISKA very limited. This is because the success of SISKA not only determined by the technology and the support of natural resources, but also by farmer characteristics. This study aims to determine the internal and external characteristics of farmers who implement systems integration; and the level of their  knowledge  of  SISKA.  This  study  uses  a  survey  to  determine  Farmers Group Patient nrimo purposive. The qualitative descriptive data analysis using ordinal scale is Likert Scale. The results show the performance of the internal characteristics of farmers by age 90.91 % are in the productive age farmers had high school education or equivalent 63.64 %, with an average tenure of 3 ha, number of dependents on average 4 persons, the average farm experience 18  years,  kekosmopolitan  including  high  category  seen  from  the  number  of resources with a score of  4.18, searching for information with a score of 4.18 and  4.45  the  motivation  for  information.  The  external  characteristics  of farmers as a whole are in the category of being seen from the intensity of the extension  with  a  score  of  4.12,  the  accuracy  of  the  channel  extension  with  a score  of  3.80,  the  number  of  resources  of  3.23,  the  price  of  the  means  of production with a score of 3, the availability of low production with a score of 1,86,  the  environmental  carrying  capacity  score  of  3.95.  The  results  of  the study indicate the level of their knowledge of SISKA including high category.